2018
DOI: 10.1002/sia.6564
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and adhesive properties of colored Ti/Zr‐based conversion coating on aluminum foil for lithium battery packaging

Abstract: In this study, an aluminum (Al) foil used for lithium ion battery packaging film was treated with titanium (Ti)/zirconium (Zr) solution containing hexafluorotitanic acid and hexafluorozirconic acid using tannic acid as a colorant and metavanadate as an accelerator, respectively, and a golden conversion coating was successfully deposited on the surface of Al foil. The morphology and composition of the coating were characterized by scanning electron microscopy, energy dispersive spectroscopy, and X-ray photoelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Currently, the mature CCP used in the market is chromate CCP [15][16][17]. However, Cr 6+ in chromate CCP is highly toxic, carcinogenic and bioaccumulative, causing great damage and a serious threat to the environment and human health [18,19]. Many countries have restricted its use [20], and the emergence of new alternative processes has become very important [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the mature CCP used in the market is chromate CCP [15][16][17]. However, Cr 6+ in chromate CCP is highly toxic, carcinogenic and bioaccumulative, causing great damage and a serious threat to the environment and human health [18,19]. Many countries have restricted its use [20], and the emergence of new alternative processes has become very important [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of hexavalent chromium is restricted by its high toxicity to humans and environmental contamination. 5 In order to overcome these problems, a number of alternative treatments are proposed using chrome-free solutions such as phosphate (P), 6,7 rare earth salt, 8 permanganate, 9 titanate/zirconate (Ti/Zr), 10,11 and molybdate (Mo). 12,13 However, some problems remain to be solved for these methods.…”
Section: Introductionmentioning
confidence: 99%
“…The coating obtained by Ti/Zr treatment is generally colorless, or the color depth is too shallow, making it difficult for naked-eye observation of the formation of the coating. 10 The conversion process using organic agents such as silane coupling agent is complicated and requires a drying temperature of over 200 C.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that zirconium conversion coatings increase the adhesiveness of substrate and the interfacial bond strength between substrate/topcoats. 15,54,[62][63][64][65][66][67] They also reduce the rate of cathodic delamination/filiform corrosion. 42,58,59,64,68 Surface cleaning or pre-treatment before application of ZrCC has an essential effect on the rate of the conversion process and the final properties of coatings.…”
mentioning
confidence: 99%